Uji Aktivitas Anti Jamur Ekstrak Kayu Manis (Cinnamomum burmanii Blume) Terhadap Jamur Candida Albicans - Nuryanti, Siti; Jura, Minarni Rama; Nursucianti, Nursucianti (Jurnal Akademika Kimia, 2015)
Cinnamon contains essential oils those can act as anti-fungal. This study aims to determine the inhibition of fungal growth of cinnamon extract against candida albicans. The study was conducted using a sample of cinnamon extract in some solvents those were distilled water, ethanol, and hexane, and the suspension of the fungus candida albicans which has been synchronized with the MC.Farland standard solution, and performed with pitting method. The results showed that the inhibition of cinnamon extract in hexane against candida albicans fungus was greater than in distilled water and ethanol. Hexane was the most dominant solvent to extract oil contained in cinnamon and some seeds, and also easy to evaporate and separate to produce more essential oils. Based on the observations the percentage of fungal inhibition of cinnamon extracts in distilled water, ethanol, and hexane solvents were, 3.19%, 0% and 100%, respectively.